2010
DOI: 10.1111/j.1365-2435.2010.01825.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative status and telomere length in a long-lived bird facing a costly reproductive event

Abstract: Summary1. Life-history theory predicts that high reproductive investment alters self-maintenance. Several mechanisms underlying the cost of reproduction have been previously suggested, but how parental effort may impact cell and organism maintenance remains largely unknown. The effects of oxidative stress -the imbalance between oxidative damage and defences -on telomere dynamics may underlie this relationship. Indeed, oxidative stress is associated with costly activities like breeding, and impacts telomere len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 43 publications
(79 reference statements)
5
112
3
1
Order By: Relevance
“…However, Beaulieu et al [54] did not detect a significant difference in telomere shortening between individuals providing differential reproductive effort in free-living Adélie penguins (Pygoscelis adeliae), induced by handicapping, and thus presumably increasing foraging costs. Further experimental work, manipulating reproductive effort, is required to establish whether there is a causal effect of reproductive effort on telomere shortening in birds.…”
Section: Discussionmentioning
confidence: 99%
“…However, Beaulieu et al [54] did not detect a significant difference in telomere shortening between individuals providing differential reproductive effort in free-living Adélie penguins (Pygoscelis adeliae), induced by handicapping, and thus presumably increasing foraging costs. Further experimental work, manipulating reproductive effort, is required to establish whether there is a causal effect of reproductive effort on telomere shortening in birds.…”
Section: Discussionmentioning
confidence: 99%
“…2), which can be measured in the circulation (Tsahar et al, 2006). As such, uric acid largely determines the total antioxidant capacity of serum (Cohen and McGraw, 2009), although non-enzymatic antioxidant capacity measured by the OXY adsorbent test does not include uric acid (Beaulieu et al, 2011). Measuring uric acid in addition to performing the OXY adsorbent test therefore provides a means to determine the importance of uric acid relative to other nonenzymatic antioxidant defenses.…”
Section: Sacrificial Moleculesmentioning
confidence: 99%
“…Beaulieu et al, 2011Jenni-Eiermann et al, 2014;Speakman, 2008;Tsahar et al, 2006). The regulation of oxidative damage may act as an underlying driver of aging or longevity (Montgomery et al, 2012;Selman et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Telomeres appear to shorten throughout the life of individuals (Pauliny et al 2006;Bize et al 2009;Salomons et al 2009;Heidinger et al 2012;Angelier et al 2013;Barrett et al 2013;Bauch et al 2013;Boonekamp et al 2014) and, importantly, telomere length (TL) has been shown to be a reliable predictor of survival under some circumstances (Haussmann et al 2005;Pauliny et al 2006;Bize et al 2009;Salomons et al 2009;Heidinger et al 2012;Angelier et al 2013;Barrett et al 2013) but not others (Pauliny et al 2006;Beaulieu et al 2011;Caprioli et al 2013;Boonekamp et al 2014). Therefore, specific attention has been paid to the determinants of TL in wild vertebrates.…”
Section: Introductionmentioning
confidence: 99%